(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
The ways of conducting grammar games are diverse, and it is necessary that they be perfectly mastered by school teachers and taught to the students themselves. Grammar games will help to eliminate difficulties in learning language material.